3,8t-(2,8t+0,7t) 3t=2,4

3,8t-(2,8t+0,7t) 3t=2,4
Гость
Ответ(ы) на вопрос:
Гость
(3.8t-2.8t-0.7t)×3t=2,4 0.9t=2.4 t=2.666
Гость
3,8t - (2,8t + 0,7t) = 3,8t - 3,5t = 0,3t                3t = 2,4 0,3t = 0,3 * 0,8 = 0,24                                        t = 2,4 : 3                                                                              t = 0,8 -------------------------------------------------------------------- 3t = 2,4 0,3t - ? 3t : 0,3t = 10 (раз) - t в 10 раз меньше 2,4 : 10 = 0,24 - результат во столько же раз меньше 0,3t = 0,24 t = 0,24 : 0,3 t = 0,8
Не нашли ответ?
Ответить на вопрос
Похожие вопросы